2020
DOI: 10.1111/hdi.12834
|View full text |Cite
|
Sign up to set email alerts
|

Serum glucose and phosphorus concentrations during continuous renal replacement therapy using commercial replacement solutions with or without phosphorus

Abstract: Introduction Continuous venovenous hemofiltration (CVVH) is a common practice in the intensive care unit often associated with electrolyte derangements. Recently, our institution added a phosphate dialysis solution, Phoxillum®, to our formulary as an option for CVVH fluid in addition to the bicarbonate‐based Prismasol® products available. We sought to evaluate the impact of Phoxillum in patients who required CVVH when compared to Prismasol with regard to phosphate and glucose management. Methods This was a sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…Glucose measurements resulting in (hyper- and hypoglycemia) were not different in the 2 groups. Our study results align with the findings of Crowley et al [22], with a significant reduction in incidence of hypophosphatemia during CRRT, and higher rates of hyperphosphatemia with the use of phosphate containing CRRT solutions. Importantly, in our study, maximum serum phosphate levels during CRRT were not different between the 2 CRRT solutions groups, which may represent that clinically significant hyperphosphatemia may have been related to other factors beyond the CRRT solution type.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Glucose measurements resulting in (hyper- and hypoglycemia) were not different in the 2 groups. Our study results align with the findings of Crowley et al [22], with a significant reduction in incidence of hypophosphatemia during CRRT, and higher rates of hyperphosphatemia with the use of phosphate containing CRRT solutions. Importantly, in our study, maximum serum phosphate levels during CRRT were not different between the 2 CRRT solutions groups, which may represent that clinically significant hyperphosphatemia may have been related to other factors beyond the CRRT solution type.…”
Section: Discussionsupporting
confidence: 92%
“…Another study by Crowley and colleagues [22] assessed the impact of phosphate containing CRRT solutions on phosphate levels and glucose measurements. This was a single-center, retrospective observational cohort study including 60 adult patients who received CRRT for ≥24 h. The incidence of hypophosphatemia (per CRRT days) in this study was higher in the non-phosphate containing CRRT solution group versus the 1 mmol/L phosphate containing CRRT solution group: 24.9 versus 6.2% (RR 0.20; 95% CI 0.10–0.42, p < 0.0001), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to hypothesize that hypophosphatemia-induced diaphragm weakness impairs respiratory function, possibly prolonging mechanical ventilation and increasing the need for tracheostomy and the risk of mortality as some studies have shown (32). Importantly, this is a modifiable risk factor in critically ill patients requiring CRRT (18,19). Differing trajectories of serum phosphate levels by patients in the two CRRT solutions groups, as depicted in Figure 2, further support this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The two primary strategies for managing phosphate during CRRT include: (1) utilizing phosphate-free CRRT solutions plus protocolized phosphate replacement or (2) a preemptive strategy with phosphate-containing CRRT solutions through compounding or the use of commercially available options (16,17). The use of preemptive phosphate replacement with phosphate-containing CRRT solutions has been associated in several studies with a reduction in the severity and duration of hypophosphatemia in patients in the ICU requiring CRRT; however, none of these studies have been large enough to observe an effect on clinical outcomes (4,15,(18)(19)(20)(21). The aim of this study was to examine the relationship between the receipt of phosphatecontaining (versus phosphate-free) CRRT solutions and clinical outcomes of ventilator dependence in a mixed adult patient population in the ICU receiving CRRT and mechanical ventilation.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the commercially available phosphate-containing CKRT solutions are formulated without dextrose. Although observational data suggest the risk of severe hypoglycemia is not significantly higher with these solutions compared with standard phosphate-free solutions with dextrose (71,72), additional glucose monitoring may be prudent. Additionally, the prolonged use of glucose-free CKRT solutions in patients not receiving nutrition can predispose to the development of euglycemic ketoacidosis, which manifests as unexplained anion gap metabolic acidosis, normal serum glucose, and ketonemia and corrects with the provision of insulin with glucose (73).…”
Section: Complications Of Ckrtmentioning
confidence: 99%